Review of "This Time is Different: Eight Centuries of Financial Folly by Carmen M. Reinhart and Kenneth S. Rogoff" - M. Ayhan Kose (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
This Time is Different: Eight Centuries of Financial Folly is one of the best, if not the best, books ever written on the history of financial crises. It presents a comprehensive survey of financial crises utilizing an extraordinary database of macroeconomic and financial series. The massive data analysis constituting the core of the manuscript leads the authors to arrive at a simple but powerful conclusion: while times change, locations change, actors change, financial crises often exhibit more similarities than differences throughout history. This conclusion nicely relates to the title of the book as it proves wrong the claim 'this time is different' that is often heard during boom times preceding crises. The book is a must read for anyone interested in economics and finance. This review presents a brief summary of the book and a discussion about its implications for future research.
Keywords: 330